The Readability of E-module Material in Teaching English for Specific Purpose of Biology Education Study Program, Muhammadiyah University of Palembang Tri Rositasari, AcengRahmat, Emzir - Rositasari, Tri; Rahmat, Aceng; ., Emzir (Advances in Social Sciences Research Journal, 2018)
This study was aimed to determine the E-module Material in Teaching English for Specific Purpose of Biology Education Study Program, Muhammadiyah University of Palembang. There are some aspects that became in indicators why module was created. One of them was to find out the readability of E-module material Teaching English for Specific Purpose of Biology Education Study Program. Therefore, this readability was tested from 3 aspects of evaluations, there were language component aspects, meaning, typing aspects, display, and publication aspects. Form all the aspects, it was found that the readability ofE-module Material in Teaching English for Specific Purpose of Biology Education Study Program, Muhammadiyah University of Palembang was effective.